NARCISSISTIC PERSONALITY DISORDER IN BRET EASTON ELLIS'S AMERICAN PSYCHO: CHARACTER ANALYSIS - Paputungan, Ahmad Sahid; Maru, Mister Gidion; Sabudu, Delli (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The purpose of this study is to analyze the Narcissistic Personality Disorder (NPD) shown by Patrick Bateman in ElliÃ¢â‚¬â„¢ American Psycho. The present study also aims to analyze the causes and effect of the NPD in the novel American Psycho written by Bret Easton Ellis. The writer employed qualitative research as the research design in which the data are collected in the form of words. To collect the research data, note taking technique is used. The primary data source in this study is the novel American Psycho written Bret Easton Ellis. The primary data is supported by the secondary data such as research papers, books, and internet. Ã‚Â In analyzing the data, the researcher used psychological criticism. From the result show in American psycho has described that Narcissistic Personality Disorder is a bad personality, not only effect to the suffer but also effect to the others. Characteristic of narcissistic personality disorder that shown by Patrick Bateman in the novel and determine the tendencies in Patrick Bateman. The effect of narcissistic personality disorder in Patrick Bateman makes him tendencies violence, a greedy person, and make him into illusion. The causes of narcissistic personality disorder are sociological factors, biological factors, and psychological factors.